Impact of Anesthetic Management on Safety and Outcomes Following Mechanical Thrombectomy for Ischemic Stroke in SWIFT PRIME Cohort - Eker, Omer F.; Saver, Jeffrey L.; Goyal, Mayank; Jahan, Reza; Levy, Elad I.; Nogueira, Raul G.; Yavagal, Dileep R.; Bonafé, Alain; , SWIFT PRIME investigators (Frontiers in Neurology, 2018)
Background and Purpose: The optimal anesthetic management of acute ischemic stroke patients during mechanical thrombectomy (MT) remains controversial. In this post-hoc analysis, we investigated the impact of anesthesia type on clinical outcomes in patients included in SWIFT PRIME trial. Methods: Ninety-seven patients treated with MT were included. Patients treated in centers with general anesthesia (GA) policy (n=32) were compared with those treated in centers with conscious sedation (CS) policy (n=65). Primary outcomes studied included times to treatment initiation (TTI), rates of successful recanalization (TICI 2b/3), and functional independence (mRS 0–2 at 90 days). Secondary outcomes were adverse events, lowest systolic and diastolic blood pressures (LSBP and LDBP) during MT. Univariate analysis and multivariate regression logistic modelling were conducted. Results: The GA-policy and CS-policy groups presented comparable TTI (94±36 min vs. 102±48 min; p=0.44), rates of TICI 2b/3 recanalization (22/32 [68.8%] vs. 51/65 [78.5%]; p=0.32). CS-policy was associated to higher rate of functional independence than GA-policy, but the difference was not significant (43/65 [66.2%] vs. 16/32 [50.0%]; p=0.18). GA-policy patients had a higher rate of postoperative pneumonia (11/32 [34.4%] vs. 8/65 [12.3%]; p=0.02) and lower LSBP (110 [30, 160] mmHg vs. 119 [77, 170] mmHg; p=0.03) and LDBP (55 [15 , 75] mmHg vs. 67 [40, 121]; p<0.001). When corrected for differences in baseline characteristics, GA-policy was associated with lower rate of functional independence (OR 0.32; p=0.05). A 10-point increase in perprocedural LDBP was associated with an increased likelihood of favourable outcome (OR 1.51; p=0.01). Conclusions: GA-policy for MT presented comparable TTI and rates of successful revascularization to CS-policy. However, GA-policy was associated with lower rates of functional independence and with higher incidence of perprocedural hypotension and postoperative pneumonia. Clinical Trial Registration : URL – http://www.clinicaltrials.gov. Unique identifier: NCT01657461.